Strategi Pembelajaran Berbasis Masalah dalam Meningkatkan Kemampuan Problem Solving Peserta Didik - Sri Wati Putri; Adillah Almufidah; Gusmaneli Gusmaneli (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
This research aims to improve and develop students' abilities to learn how to think critically in finding solutions to problems. Based learning strategy is a learning strategy that invites students to learn independently, carry out discussions, find solutions to solve problems and be able to draw conclusions. This research aims to examine more deeply problem-based learning strategies so that students can develop their abilities to overcome complex and diverse problems. The data collection used by researchers is a literature study by studying and citing several sources from textbooks, articles, journals, modules and other publications. The use of this learning strategy is expected to improve students' problem solving abilities.